Intrapreneurship as an enabler to improve performance in the video entertainment industry: A Pay-Tv African Context - Ngwenya, Sibongile (University of the Witwatersrand, Johannesburg, 2024)
This research study investigated the relationship between intrapreneurship and two internal factors within an organisation organisational that lead to improved business performance. The organisational internal factors that were investigated are management support and organisational culture. The theoretical background to the study was adopted and grounded on the theory of corporate entrepreneurship, while the study focuses on Pay-Tv within the African context for a giant media player MultiChoice Group. The study was based on a quantitative approach, implementing existing instruments and analysing a sample of two hundred and seventy-one (271) employees. The results presented a significant and positive relationship exists between the organisational culture and intrapreneurship and A positive relationship exists between management support and intrapreneurship. This study contributes to the research theory of corporate entrepreneurship by recognizing the influence and importance of the organisational internal factors in improving business performance within the Pay-Tv industry. The study Industry players, industry employees, and academic practitioners Intrapreneurship principles a practice that can be implemented to facilitate and encourage the adoption of intrapreneurship to drive overall improved business performance. The study is relevant to the industry players who seek to remain entrepreneurial, and competitive and contribute to the industry’s sustainability into the future
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Entrepreneurship and New Venture Creation to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Intrapreneurship; Management support; Innovation; Performance; PayTV; UCTD; SDG-8: Decent work and economic growth